Online flipped learning methods for teaching hospitality skills and management practices in an epidemic situation: A study on learning attitude and effectiveness - Chen, Kuo-Wei; Wang, Ze-Yung (Frontiers in Psychology, 2023)
Starting in 2019, the ongoing COVID-19 pandemic has lasted 3 years and will likely continue to affect the lives of people all over the world. According to a United Nations Educational, Scientific and Cultural Organization (UNESCO) survey, more than 91% of students from all over the world have been affected by the spread of COVID-19. The application of technological networks can help solve problems related to being unable to attend school in person, as online teaching can effectively help reduce learning loss in the short term. In Taiwan, the higher education system has been using online learning, but now faces a new and huge crisis, as some courses do not readily translate to this setting. In professional courses run by hospitality departments, it is essentially impossible to accurately convey the practical skills required, for example, aspects of color, aroma, and taste through online teaching. Moreover, the learning level of each student varies greatly. During the online teaching process, instructors teach professional skills and movements through a single teaching video, which may not meet the needs of all students. In response, this study explores using the flipped teaching method, to not only enable students to master and control their learning and effectively adjust their self- adaptive learning progress but also to help teachers solve problems and impart professional skills using a two-way, interactive, online teaching method. This approach, flipping a class in an online learning environment, could effectively make up for the one-way teaching sometimes created by video content, and address the problem of gaps in learning professional practical skills. It can also induce students with poor learning attitudes to actively participate in learning. This study involved 55 bachelor students from a university of science and technology in Taiwan. The research results are as follows: (1) Students who participated in the flipped teaching mode, which involved two-way interaction showed better professional understanding of the course and improved willingness to learn, thereby improving the learning effect. (2) Awareness of these poor practical catering professional skills in students, assisted in laying the professional foundation for students to gradually improve their learning attitude and their advanced skills. This indicates that students with poor academic performance in an online environment might benefit from two-way interactive teaching. Teachers should clarify detailed descriptions of professional practical actions that confuse students. (3) In flipped learning, the grouping of “game/toy-based e-learning” can not only improve the performance of students who actively study to achieve good grades but also help and motivate other students to learn together. These results indicate that in flipped classrooms that use an online learning environment, the active learning and learning attitudes of students were positive and that their interest in learning and learning efficiency was also significantly improved. At the same time, this approach stimulated the innovation, creativity, and creative development of students in using professional technology in the hospitality industry. It transformed the passive learning situation of online one-way teaching into an active two-way teaching environment.